Christian Participation and Creative Resistance: Reflecting on Luther's Two‐fold Governance in Muslim‐Majority Malaysia. Issue 3 (4th September 2017) - Kit, Sivin
Abstract: How can Luther's contribution in theology and lessons arising from the Reformation have any relevance for Christians in Muslim‐majority Malaysia? In this article, I propose that a reflection on Luther's understanding of the so‐called "doctrine of two kingdoms"—better understood as God's two‐fold governance—offers a critical contribution that not only is relevant for the Malaysian Christian community, but also may have intercultural and interreligious implications for dialogue and engagement with the Muslim majority for interreligious solidarity and the common good.